ResilienceP Analysis: Bounding Cache Persistence Reload Overhead for Set-Associative Caches - Aftab Rashid, Syed (2020)
This work presents different approaches to calculate CPRO for set-associative caches. The PCB-ECB approach uses PCBs of the task under analysis and ECBs of all other tasks in the system to provide sound estimates of CPRO for set-associative caches. The resilienceP analysis then removes some of the pessimism in the PCB-ECB approach by considering the resilience of PCBs during CPRO calculations. We show that using the state-of-the-art (SoA) resilience analysis to calculate resilience of PCBs may result in underestimating the CPRO tasks may suffer. Finally, we have also presented a multi-set alike resilienceP analysis that highlights the pessimism in the resilienceP analysis and provides some insights on how it can be removed.